Legal Politics of Child Participation in the Public Policy Process in Batang Regency: A Study of the Implementation of the Principles of Child Protection - Nofita Sari (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
This research analyses the legal politics of children's participation in public policy in Batang District, focusing on the gap between normative recognition and practical implementation. Although Indonesia has ratified the Convention on the Rights of the Child (KHA) and adopted it in the Child Protection Law, children's participation rights are still reduced, as seen in the vagueness of Article 10 of Law No. 23/2002 which limits participation based on ‘decency and propriety’. This qualitative study combines legal document analysis, participatory observation at the Children's Forum and Musrenbang (2018-2024), as well as stakeholder interviews, to find that children's participation in Batang District-despite being recognised as a Child Friendly District-is symbolic. Key challenges include a lack of stakeholder understanding, manipulation of children's voices, and the absence of a follow-up mechanism for aspirations, which is reflected in the omission of participation indicators in the Regional Action Plan. The research concludes that there is a need to strengthen ratification of the KHA, constitutional amendments to recognise children's right to be heard, and local policy reforms that guarantee space for meaningful participation. The findings emphasise the urgency of a holistic approach in the politics of child protection law.